“Beyond just the four walls of the clinic”: The roles of health systems caring for refugee, immigrant and migrant communities in the United States - Abudiab, Seja; de Acosta, Diego; Shafaq, Sheeba; Yun, Katherine; Thomas, Christine; Fredkove, Windy; Garcia, Yesenia; Hoffman, Sarah J.; Karim, Sayyeda; Mann, Erin; Yu, Kimberly; Smith, M. Kumi; et al. (Frontiers in Public Health, 2023)
This article is part of the Research Topic ‘Health Systems Recovery in the Context of COVID-19 and Protracted Conflict’ Introduction Refugee, immigrant and migrant (hereafter referred to as “immigrant”) communities have been inequitably affected by the COVID-19 pandemic. There is little data to help us understand the perspectives of health systems on their role, in collaboration with public health and community-based organizations, in addressing inequities for immigrant populations. This study will address that knowledge gap. Methods This qualitative study used semi-structured video interviews of 20 leaders and providers from health systems who cared for immigrant communities during the pandemic. Interviewees were from across the US with interviews conducted between November 2020–March 2021. Data was analyzed using thematic analysis methods. Results Twenty individuals representing health systems participated with 14 (70%) community health centers, three (15%) county hospitals and three (15%) academic systems represented. The majority [16 health systems (80%)] cared specifically for immigrant communities while 14 (70%) partnered with refugee communities, and two (10%) partnered with migrant farm workers. We identified six themes (with subthemes) that represent roles health systems performed with clinical and public health implications. Two foundational themes were the roles health systems had building and maintaining trust and establishing intentionality in working with communities. On the patient-facing side, health systems played a role in developing communication strategies and reducing barriers to care and support. On the organizational side, health systems collaborated with public health and community-based organizations, in optimizing pre-existing systems and adapting roles to evolving needs throughout the pandemic. Conclusion Health systems should focus on building trusting relationships, acting intentionally, and partnering with community-based organizations and public health to handle COVID-19 and future pandemics in effective and impactful ways that center disparately affected communities. These findings have implications to mitigate disparities in current and future infectious disease outbreaks for immigrant communities who remain an essential and growing population in the US.